Study on Corrosion Resistance and Welding Properties of High Strength, Tough Bainite Steel CB10 - Cheng, Xiao-Le; Zhou, Si-Jun; Xu, Guang-Shen; Fu, Han-Guang; Bai, Bing-Zhe (Frontiers in Materials, 2019)
In order to gain the high strength and toughness bainite steel, author reported on their own developed CB10 steel. The CB10 steel was heat treated at different tempering temperatures to control the microstructure and mechanical capabilities, and further its variation regular pattern were explored. The results showed that bainite, ferrite and M/A island could be engendered when CB10 steel was tempering at 250℃, 450℃, 600℃ and 670℃, respectively. With the increase of tempering temperature, lath-type bainite was obviously began to merge and coarsen, as well as polygonal ferrite was appeared. When the tempering temperature was above 600℃, recovery and re-crystallization were occurred in some regions. In particular, the mechanical properties of CB10 steel were the best at 450℃ tempering temperature, among them its tensile strength was 632 MPa, the yield strength was 487MPa, the elongation was 25%, and the Charpy absorbed energy was greater than 140J. As following, anti-HIC and weldability of CB10 steel were tested. The results indicated that there was no cracks on the surface of sample, displaying excellent anti-HIC and weldability performance. Moreover, the maximum hardness of HAZ was 231Hv, the maximum Charpy absorbed energy was 285.0J, and fracture morphology all belonged to ductile fracture when the impact temperature was above -60℃.